Evaluation of Hot Water Treatments for Management of Ditylenchus dipsaci and Fungi in Daffodil Bulbs - Qiu, J (Journal of nematology, 1993)
Treatment of daffodil (Narcissus pseudonarcissus) bulbs in a 0.37% formaldehyde water solution at 44 C for 240 minutes is a standard practice in California for management of the stem and bulb nematode, Ditylenchus dipsaci. Recent concern over the safety of formaldehyde and growers' requests for a shorter treatment time prompted a reevaluation of the procedure. The time (Y, in minutes) required to raise the temperature at the bulb center from 25 to 44 C was related to bulb circumference (X, in cm) and is described by the linear regression Y = -15 + 3.4X. The time required for 100% mortality of D. dipsaci in vitro without formaldehyde was 150, 60, and 15 minutes at 44, 46, and 48 C, respectively. Hot water treatment (HWT) with 0.37% formaldehyde at 44 C for 150 minutes controlled D. dipsaci and did not have a detrimental effect on plant growth and flower production. Shorter formaldehyde-HWT of 90, 45, and 30 minutes at 46, 48, and 50 C, respectively, controlled D. dipsaci but suppressed plant growth and flower production. Fungal genera commonly isolated from the bulbs in association with D. dipsaci were Penicillium sp., Fusarium oxysporum f. sp. narcissi, and Mucor plumbeus, representing 60, 25, and 5%, respectively, of the total fungi isolated. These fungi caused severe necrosis in daffodil bulbs. HWT at 44 C for 240 minutes reduced the number of colonies recovered from bulbs. The effects of formaldehyde, glutaraldehyde, and sodium hypochlorite in reducing the population of fungi within bulbs were variable. Satisfactory control of D. dipsaci within bulbs can be achieved with HWT of bulbs at 44 C for 150 minutes with 0.37% formaldehyde or at 44 C for 240 minutes without chemicals